2019
DOI: 10.1093/mmy/myz086
|View full text |Cite
|
Sign up to set email alerts
|

Placental and breastmilk transfer of voriconazole to offspring from pregnant and lactating bottlenose dolphins (Tursiops truncatus)

Abstract: Fungal pneumonia is a common disease in bottlenose dolphins (Tursiops truncatus), including pregnant and lactating ones. Voriconazole (VRCZ) is commonly used to treat respiratory fungal infections in this species; however, it is unknown whether VRCZ is transferred via the placenta and breastmilk and whether its usage is safe in pregnant and lactating dolphins. We measured VRCZ concentrations in breastmilk and dams’, umbilical cord, and calves’ plasma samples from four dam-calf dolphin pairs in the Port of Nago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…At their inception, Japanese zoos did not have many employees with degrees other than veterinarians, and many directors of zoos were also veterinarians, but in recent years, the number of staffs with university or higher degrees and with curatorial qualifications has been increasing [ 17 , 19 ]. As the number of papers written in English by the staff of zoos or aquariums is also increasing ( Figure 3 ), even at institutions that do not employ full-time researchers, e.g., [ 20 , 21 ], it can be concluded that the efforts of many staff are supporting JAZA’s international research challenge.…”
Section: Discussionmentioning
confidence: 99%
“…At their inception, Japanese zoos did not have many employees with degrees other than veterinarians, and many directors of zoos were also veterinarians, but in recent years, the number of staffs with university or higher degrees and with curatorial qualifications has been increasing [ 17 , 19 ]. As the number of papers written in English by the staff of zoos or aquariums is also increasing ( Figure 3 ), even at institutions that do not employ full-time researchers, e.g., [ 20 , 21 ], it can be concluded that the efforts of many staff are supporting JAZA’s international research challenge.…”
Section: Discussionmentioning
confidence: 99%